Can a deportation policy backfire? - Oded Stark; Lukasz Byra (University of Bonn, Center for Development Research (ZEF), 2019)
Drawing on a model in which utility is derived from consumption and effort (labor supply), we ask how the deportation of a number of undocumented migrants influences the decisions regarding labor supply, consumption, and savings of the remaining undocumented migrants. We assume that the intensity of deportation serves as an indicator to the remaining undocumented migrants when they assess the probability of being deported. We find that a higher rate of deportation induces undocumented migrants to work harder, consume less and, as a result of those responses, to save more. Assuming that the purpose of deportation policy is to reduce the aggregate labor supply of undocumented migrants in order to raise the wages of low-skilled native workers, we conclude that the policy can backfire: an increase in the labor supply of the remaining undocumented migrants can more than offset the reduction in the labor supply arising from the deportation of some undocumented migrants. Simulation shows that if the number of deportations in relation to the size of the undocumented migrant workforce is small, then the combined effect of the reduction in the labor supply of the deportees and the increase in the labor supply of the remaining undocumented migrants can be that the aggregate labor supply of undocumented migrants will increase. It follows that an effective deportation policy has to involve the expulsion of a substantial proportion of the total number of undocumented migrants in the workforce.
Keywords: D81; E21; F22; J61; J78; 330; Consumption of undocumented migrants; Labor supply of undocumented migrants; Savings of undocumented migrants; Aggregate labor supply of undocumented migrants; Efficacy of a deportation policy of a number of undocumented migrants